Meningkatkan Kemampuan Menulis Surat Resmi pada Siswa Sekolah Dasar Melalui Pembelajaran Kontekstual (CTL) - Rumanti Pintubatu; Fahmi Ashari S Sihaloho; Syarifah Ainun Harahap (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2021)
This study explores the effectiveness of the Contextual Teaching and Learning (CTL) method in enhancing the ability of fifth graders at SDN No. 101906 Pagar Jati to write official letters. Traditional teaching methods, where the teacher predominantly lectures and students passively listen and take notes, have been found insufficient in developing the necessary competencies for effective letter writing. CTL, by integrating real-life contexts into learning, promises a more engaging and effective approach. This action research, conducted over two cycles, utilized observation, written tests, and documentation as methods of data collection. Findings indicated significant improvements in students' writing abilities from 43.75% competency in the first cycle to 81.25% in the second, showcasing CTL’s potential to significantly transform educational practices and outcomes.